Adopting International Financial Reporting Standards (IFRS) in Africa: benefits, prospects and challenges. (1st January 2012) - Owolabi, Akintola; Iyoha, Francis O.
This paper presents the findings of an empirical study on the benefits, prospects and challenges of adoption of International Financial Reporting Standards (IFRS) in some African countries. A questionnaire was administered to gather data from respondents made up of users and preparers of accounting information using the Twitter social network. The objective was to find out the perception of users and preparers about what the benefits, prospects and challenges of IFRS adoption are in African countries. The results of the study indicate that IFRS adoption in Africa will have the potential to be beneficial to a wide range of stakeholders. The benefits notwithstanding, there are however, a number of challenges to be faced in the process of adoption of the new standard including the ethical environment in Africa. The study recommends among others that a rigorous IFRS capacity building programme should be embarked upon by all regulatory bodies, firms and training institutions in order to provide the needed manpower for IFRS implementation, monitoring and compliance.